Trophic ecology of Loricariichthys melanocheilus Reis & Pereira, 2000 (Siluriformes: Loricariidae) in Ibicuí river, southern Brazil - Éverton Luís Zardo (Acta Scientiarum. Biological Sciences, 2016)
bimonthly samples were taken in lotic and lentic ecosystems. Fish were caught and fixed in 10% formalin and dissected for stomach content analysis. Items were identified to the lowest taxonomic level possible. Stomach fullness (SF), repletion index (RI) and intestinal quotient (IQ) were estimated. Diet was assessed by the frequency of occurrence and the volumetric method, combined to obtain a Alimentary index. Feeding activity was analyzed with mean values of SF, RI and vacuity index (VI), which represents the percentage of empty stomachs. These parameters were compared seasonally, spatially, and according to the circadian rhythm. The main items in the trophic spectrum of L. melanocheilus were detritus, sediment, plant organic matter, nematodes, micro crustaceans (Copepoda, Cladocera) and insects (Diptera, Trichoptera, Ephemeroptera and Odonata). No environmental or seasonal variations were found for the consumed items. Feeding activity showed seasonal and environmental variations according to RI but did not significantly change according to SF. The IQ was 1.51, and showed seasonal variations, indicating changes in the diet.